HOW CAN WE USE NEUROTRANSMITTERS IN EMOTION AND REWARD SYSTEM TO STUDY DEPRESSION? - Zhang, Pan (LIFE: International Journal of Health and Life-Sciences, 2019)
Depression is the most common and widespread psychiatric disorder severely affecting people’s lives at all ages. Factors from social, psychological, and biological aspects can contribute to depression, and many hypotheses are associated with biological factors involved in the aetiology of depression such as genes and neurotransmitters. As three monoamine neurotransmitters, dopamine, serotonin, and norepinephrine, are involved in the regulation of mood and motivation in emotion and reward system, the dysfunction of neurotransmitters of depressive patients can lead to their abnormal symptoms. This paper will discuss how the behaviour of these neurotransmitters has helped develop antidepressant drugs for treating depression. Although helpful, antidepressant drugs have other negative health outcomes on users such as side effects. Research on antidepressants has led to the development of new drugs such as nasal spray and skin patch which has shown to alleviate symptoms of depressive patients. Current treatments with a potential reduction of side effects are suggested on new applications for improving public health condition. Furthermore, other non-medical factors such as social engagement and physical activity are also involved in treating depression.